If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -4 + 5n + -12 = 2 Reorder the terms: -4 + -12 + n + 5n = 2 Combine like terms: -4 + -12 = -16 -16 + n + 5n = 2 Combine like terms: n + 5n = 6n -16 + 6n = 2 Solving -16 + 6n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 6n = 2 + 16 Combine like terms: -16 + 16 = 0 0 + 6n = 2 + 16 6n = 2 + 16 Combine like terms: 2 + 16 = 18 6n = 18 Divide each side by '6'. n = 3 Simplifying n = 3
| 4(a+1)=3(a+3) | | 5(6)+6=30 | | 3(t+3)+4(3t)=-6 | | -2(u+3)=3u+14 | | t+(t+4)(-4)=t-4 | | (x-6)^((3)/(2))=125 | | 3mn+4m+2mn= | | -3x-(5x+5)=-13 | | 4x+x+2=10x-5x+2 | | -5x-(4x-4)=31 | | 2n+3=4n+9 | | A=ha | | t-(5t-3)=-9 | | (5y/3)^2-y^2=21 | | t-(5t+3)=-9 | | (-2x+7)(7x+2)=0 | | -1-(-3+5n)=7-5(4+4n) | | -(3x+2)-(3x-4)=-8-(2x+2) | | 11x-8+2x+3=x+4+12x-9 | | 0.32x+0.39y=3.62 | | (2x-7)(-7x-2)=0 | | -(2x-1)-(4x+4)=-10-(2x+5) | | 3(y-3)-(5y-2)=4(3y-3)-9 | | 3(y-4)-(2y-3)=4(2y+2)+11 | | -5-2p=-4 | | Ax+B=2A-5x | | 6x+(-2)(2)=18 | | 0.4a+.5(20-a)=9.5 | | 6x+2(2)=18 | | 5(1-2b)+5(2b+5)=1 | | 0.1a+0.2(12-a)=1.9 | | 6x-2(-1)=18 |